Analyzed of the Quality of Midterm Exam I Questions for Grade VII Science Subjects in SMP Negeri 34 Padang in Academic Year 2018/2019 - Zalik Muhammad Latif; Helendra Helendra; Relsas Yogica; Armen Armen (Universitas Negeri Padang, 2019)
Researchers conduct research with the aim of determining the quality of goods in terms of analysis: 1) reliability, 2) content and empirical validity, 3) distinguishing features, 4) difficulty levels, and 5) differentiating functions. This research is descriptive research. Based on the results of data analysis, the results for review aspects: 1) reliability including high category, 2) empirical validity 52.5% valid and 47.5% invalid, 3) level of difficulty, 1 question (2.5%) category very easy , 11 questions (27.5%) medium category and 28 questions (70%) categorized as difficult, 4) Distinguishing power, obtained with different power values, namely 24 questions (60%) including good categories and 16 questions (40%) which not included in the good category, 5) the fraudulent option that does not meet the requirements is 7.5% and the one who meets the requirements is 92.5%. It can be concluded that the first semester midterm of Grade VII science subjects in SMP Negeri 34 Padang in the 2018/2019 academic year did not meet the criteria.